Antibacterial effect of extracts of Prunus salicifolia (Capulli) and Vaccinium floribundum (Mortiño) on strains of Streptococcus Mutans: In vitro study - Ivonne Yesenia Reyes; Víctor Alexander Cruz; Marlon Reinaldo Castro; Stalin Gustavo Santacruz; Clara Elena Villacres; Ana Del Carmen Armas (Kiru)
Objectives: To evaluate the halos of inhibition of the effect of extract of the skin and pulp of Prunus salicifolia (Capulli) and Vaccinium floribundum (Mortiño) on strains of Streptococcus mutans ATCC 35668 vs. Chlorhexidine gluconate 0.12%. Material and method: In Petri dishes seeded with strains of Streptococcus mutans, 20 felt disks impregnated with Prunus salicifoli, V. floribundum and chlorhexidine gluconate were placed, the evaluation of the inhibitory effect was carried out at 24 and 48 hours of incubation. The data obtained were analyzed by ANOVA and Kruskal Wallis test. Results: No statistically significant difference was found in the antibacterial effect at 24 and 48 hours between the type of fruit -c apulí and mortiño-, the anatomical part -shell and pulp- and chlorhexidine gluconate (p> 0.05) Conclusions: The extracts of Prunus salicifolia (Capulli) and Vaccinium floribundum (Mortiño) obtained both from pulp and skin have an antibacterial effect in vitro, at 24 and 48 hours, on strains of Streptococcus mutans, similar to that of chlorhexidine at 0.12% used as a control.